0498 Intravenous Iron Therapy in the Pediatric Sleep Clinic: A Single Institution Experience. (25th May 2022) - Ingram, David; AL-Shawwa, Bahauddin; Sharma, Mukta
Abstract: Introduction: Initial reports of intravenous (IV) iron administration have been promising for children with restless legs syndrome (RLS), periodic limb movement disorder (PLMD), and restless sleep. The aim of the current study was to further evaluate the clinical response to IV iron supplementation in children seen in a pediatric sleep clinic. Methods: We performed a retrospective chart review of children cared for in a single pediatric sleep clinic who also underwent IV iron infusion. Data regarding their sleep symptoms and ferritin levels were abstracted. Results: Overall, 63 pediatric sleep patients underwent IV iron infusion, mostly with ferric carboxymaltose (n=60). Of the 59 patients with clinical follow-up, 39 (73%) noted improvement in at least one symptom, and 14 (26%) did not notice improvement or noticed worsening symptoms. Of the 59 patients with pre- and post-infusion labs, the average ferritin level increased from 21.7+/-13.3 to 147.9+/-120.9, p<0.001. Comparing patients who experienced clinical improvement versus those who did not, there were no statistically significant differences in change in ferritin levels (176.6+/-127.7 vs 120.5+/-118.1, p=0.278), sex (68% in females vs 77% in males, p=0.452), or age (8.8+/-5.9 vs 7.0+/-5.1, p=0.391). In terms of immediate adverse reactions to the IV infusion, 7 (11%) experienced at least 1 side effect, with the most common being behavior change (n=6) or gastrointestinal discomfort (n=4); no episodes of anaphylaxis or extravasation were noted. Conclusion: These data provide additional support for the efficacy and safety of IV iron for pediatric RLS, PLMD, and restless sleep recalcitrant to oral iron. Support (If Any):